Feedback challenges and strategies in EFL classroom: Insights from non-formal education institution - Hidayat, Muhammad; Umalihayati, Umalihayati; Hilman, Hilman; Rachman, Aditya (Universitas Muhammadiyah Malang, 2024)
Feedback has a crucial position in supporting the success of teaching and learning processes in English as Foreign Language (EFL) classroom setting. In addition, research in this essential topic should be conducted continuously. Most research on topic have been done at schools or even universities. Only few studies concentrate in non- formal education institution such as English courses. Therefore, it is reasonable to conduct this study. Employing qualitative research, this study invited eight English teachers at non-formal education institution. The study used interview as the instrument to collect data and thematic content analysis to analyze the data. The findings displayed that the participants faced challenges and having strategies in providing feedback for students. The result revealed that teachers find challenges like inappropriate response from the students and insufficient time to make it happen fully. Then, the strategies implemented to fulfill these challenges are sharing appreciation towards students’ work at the beginning, making a clear follow-up session as well as having a clear information to students, and creating a direct comment to students’ work and also adding some notes. This study will contribute more not only for non-formal education institution but also for formal education in general. Furthermore, other aspects, such as teaching approach as well as the method used may be considered as important to adjust with these findings.